2013
DOI: 10.1016/j.ijgo.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lethal pulmonary hypoplasia among high‐risk fetuses via 2D and 3D ultrasonography

Abstract: Among high-risk fetuses, US-FLW by 2D/3D and o/e-Tot-FLV by 3D ultrasonography were more accurate than 2D parameters for predicting LPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…We chose sonographic FLV/EFW measurements to assess fetal lung development because previous studies suggested that this parameter was more accurate and feasible than other ultrasonographic parameters . The sonographic FLV/EFW parameter involved estimated fetal lung volumes measured by 3D‐US and adjusted for 2D‐US‐estimated fetal weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose sonographic FLV/EFW measurements to assess fetal lung development because previous studies suggested that this parameter was more accurate and feasible than other ultrasonographic parameters . The sonographic FLV/EFW parameter involved estimated fetal lung volumes measured by 3D‐US and adjusted for 2D‐US‐estimated fetal weight.…”
Section: Discussionmentioning
confidence: 99%
“…We chose sonographic FLV/EFW measurements to assess fetal lung development because previous studies suggested that this parameter was more accurate and feasible than other ultrasonographic parameters. 8,9 The sonographic FLV/EFW parameter involved estimated fetal lung volumes measured by 3D-US and adjusted for 2D-US-estimated fetal weight. Ruano et al 11 reported that the sensitivity and specificity of sonographic FLV/EFW for diagnosing pulmonary hypoplasia were 91.7% and 91.3%, respectively, and the accuracy was 91.4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both techniques are effective, the stacked contour method is more reproducible than VOCAL . When fetal weight is taken into account, 3D fetal lung volume measurement performs better . Furthermore, it has been suggested that 3D ultrasound adds additional value to prenatal assessment of fetal skeletal dysplasias as it has the potential to delineate subtle skeletal anomalies .…”
Section: Other Imaging Aids To Sonographic Diagnosis Of Skeletal Dyspmentioning
confidence: 99%
“…35,36 When fetal weight is taken into account, 3D fetal lung volume measurement performs better. 37,38 Furthermore, it has been suggested that 3D ultrasound adds additional value to prenatal assessment of fetal skeletal dysplasias as it has the potential to delineate subtle skeletal anomalies. 39 Both 2D and 3D ultrasonography have limitations in the presence of a high maternal body mass index, excessive fetal movements and thoracic shadowing, particularly at later gestational ages.…”
Section: Other Imaging Aids To Sonographic Diagnosis Of Skeletal Dymentioning
confidence: 99%